The role of social work specialists in the implementation of the national social policy: problems and prospects - БордіянЯ. I. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2016)
In the article it is researched the problems of the national system of social work and provision of social services as well as the means of their solving. It is shown the role of the institute of social work specialists in the implementation of tasks of the state social policy in Ukraine.